2004
DOI: 10.1016/j.ydbio.2003.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Loss of AP-2α impacts multiple aspects of ventral body wall development and closure

Abstract: Human birth defects involving the ventral body wall are common, yet little is known about the mechanism of body wall closure in mammals. The AP-2alpha transcription factor knock-out mouse provides an exceptional tool to understand this particular pathology, since it has one of the most severe ventral body wall closure defects, thoracoabdominoschisis. To gain insight into the complex morphological events responsible for body wall closure, we have studied this developmental process in AP-2alpha knock-out mice. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 76 publications
0
68
0
1
Order By: Relevance
“…Manley et al (2001) demonstrated an unsuccessful fusion of the bilateral anlagen of the sternum in hoxb4 mutant mice. Likewise, in AP-2alpha transcription factor knock-out mice, the unsuccessful midline fusion occurs because the abdominal band (rectus muscle anlagen) as well as the covering abdominal epidermis fails to develop (Brewer and Williams, 2004). These references suggest that a midline fusion of the sternal body is regulated by somite derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Manley et al (2001) demonstrated an unsuccessful fusion of the bilateral anlagen of the sternum in hoxb4 mutant mice. Likewise, in AP-2alpha transcription factor knock-out mice, the unsuccessful midline fusion occurs because the abdominal band (rectus muscle anlagen) as well as the covering abdominal epidermis fails to develop (Brewer and Williams, 2004). These references suggest that a midline fusion of the sternal body is regulated by somite derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that Hox genes could be regulated by retinoic acid (RA) indicated by various experimental systems (Kessel and Gruss, 1990;Yashiro et al, 2004). As for another retinoic acid-inducible transcription factor, Ap-2, the AP-2␣ knockout mice also exhibit severe ventral body wall closure defects (Schorle et al, 1996;Zhang et al, 1996;Brewer and Williams, 2004b). These results raise questions about possible regulatory cascades among such genes for ventral body wall formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has thus been speculated that GT development requires correct adjacent tissue differentiation, such as lower body wall formation. Abnormal lower body wall formation associated with bladder/cloaca extrophy often simultaneously displays genital abnormalities such as the upper GT defects, and epispadias (Zhang et al, 1996;Brewer and Williams, 2004;Ogi et al, 2005;Haraguchi et al, unpublished results). In relation with such phenotypes, the presence or absence of cell migration between the umbilical region (later the lower body wall) and the (upper) GT bud requires further analyses.…”
Section: Appendage Phenotype Elicited By Aberrant Growth Factor Gene mentioning
confidence: 96%